Alexander Friedman's Cosmology of Expanding and Contracting Universe (Global Journal of Science Frontier Research, 2019)
Einstein's theory of general relativity Friedman found periodic solutions of the Einstein's equations of general relativity, which periodically expanding and contracting Universe. It Freidman's dynamic concept, but even 90 years later we still haven't embraced it. compares the Friedman's dynamic concept of ancient cosmology of periodically expanding and contracting Universe Hindu astronomy Surya Siddhanta. agreement with the ancient astronomy. Even Friedman's rough cycle of expansion and contraction of the Universe (10 billion years) is as ancient exact number 8.64 billion years.
Keywords: alexander friedman’s cosmology; periodically expanding and contracting Universe; ancient cosmology of expanding and contracting universe